Optimization of Electrophotographic Toner Using Reduced Graphene Oxide and Palm Shell Carbon Aerogel - Ginting, Delovita; Billah, Salsa; Fadli Syahputra, Romi (Photon: Jurnal Sain dan Kesehatan, 2026)
Toner is a powdered ink used in electrophotographic printing technology. This research aims to develop an electrophotographic toner based on carbon aerogel composite of palm shell activated carbon enriched with reduced graphene oxide and polyester resin. Carbon aerogel synthesis was carried out through chemical activation and carbonization process, while toner formulation used Emulsion Aggregation (EA) method. Characterization results showed that the density of toner was 1,31 g/cm3 and toner was 0,81 g/cm3, porosity reached 88%, and the highest electrical conductivity was 18.246 μS/cm. These findings indicate that the integration of carbon aerogel and reduced graphene oxide in toner formulations results in densities close to the range of commercial toners as well as higher porosity than hydrocolloid-based toners. The toner formulation in this study has the potential to support the efficiency of toner usage and printing without reducing the quality of the printed output.